Selection for milk constituents in dairy cattle - Juga, Jarmo (Agricultural and Food Science, 1990)
Alternative selection combinations of milk traits were studied by the selection index method. The current pricing system in Finland does not encourage weighting fat or protein content, while the most profitable objective, when looking at farmer’s net income, is breeding for milk yield. Because of low protein content in milk and consumer attitudes, which prefer protein to fat, the main objective in the Finnish dairy cattle breeding program is protein yield. Selection for protein yield changes the protein to fat ratio to desirable direction by increasing the protein content and decreasing the fat content. Changes in constituents are small though. Changing the breeding objective from protein yield to protein content would require a considerable change in the pricing system.